Genome sequencing analysis of a family with a child displaying severe abdominal distention and recurrent hypoglycemia. Issue 3 (23rd January 2020) - Liu, Jidong; Ding, Guolian; Zou, Kexin; Jiang, Ziru; Zhang, Junyu; Lu, Yunhua; Pignata, Antonella; Venner, Eric; Liu, Pengfei; Liu, Zhandong; Wangler, Michael F.; Sun, Zheng
Abstract: Background: Germline mutations in PTEN are associated with the PTEN hamartoma tumor syndrome (PHTS), an umbrella term used to describe a spectrum of autosomal‐dominant disorders characterized by variable phenotypic manifestations associated with cell or tissue overgrowth. We report a boy who developed severe progressive abdominal distention due to a dramatic adipose mass from the age of 7 months and developed recurrent hypoinsulinemic hypoglycemia that led to seizures at the age of 4 years. Methods: Trio‐based whole‐genome sequencing was performed by using blood DNA from the child and his parents. The possible pathogenic variants were verified by Sanger sequencing. Functional characterization of the identified variant was completed by western blot. Results: The child inherited a single‐nucleotide deletion NM_000314.6:c.849delA (p.Glu284Argfs) in the tumor suppressor gene PTEN from his father. The paternal family members have a history of cancer. It is conceivable that PTEN loss‐of‐function induced the adipose tumor growth and hypoglycemia, although the proband did not meet the usual diagnosis criteria of Cowden syndrome or Bannayan–Riley–Ruvalcaba syndrome that are characterized by germline mutations of PTEN . Conclusion: This case underlines the variability of phenotypes associated with PTEN germline mutations and provides useful information for diagnosis and genetic counseling of PTEN ‐related diseases for pediatric patients. Abstract : We report a unique combination of drastic phenotypes from a pediatric patient who presented with massive abdominal distention and severe hypoglycemia that led to recurrent seizures. Trio‐based sequencing analysis identified a heterozygous germline single‐nucleotide deletion mutation in the coding region of the tumor suppressor gene PTEN.